Financial Clusters and FinTech Agglomerations – Location Factors - Włodarczyk, Michał (Journal of Finance and Financial Law, 2020)
The purpose of this work is to classify the factors responsible for the location and development of financial clusters, detailing the FinTech agglomeration. For this purpose they have been classified innovations, their sources and innovativeness, which play a key role in the development of FinTechs. A strong link has been demonstrated between the high level of innovation on a regional scale and the creation of FinTech industry centers. In addition, a proactive and modern approach to the regulatory issue was a factor conducive to the development of the studied financial clusters.